2021
DOI: 10.1089/tmj.2020.0267
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Year Single-Institution Experience Integrating Telehealth Into Urologic Care Delivery

Abstract: Objective: Telehealth is increasingly used in urology, but few studies have evaluated how it can be integrated with urology face-to-face (FTF) encounters and primary care (PC). We describe the 5-year experience of a Veterans Affairs urology service that has incorporated telehealth into their patient care program. Methods: We performed a retrospective review of encounters from 2013 to 2018 in telehealth urology clinics. To examine the way telehealth and FTF visits were utilized together, the key components of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“… 103 A study of a single institution’s VA data found that the most common reasons for urologic telehealth referrals were sexual dysfunction (26.8%), lower urinary tract symptoms (20.6%), hematuria (15.0%), prostate cancer (13.3%), and elevated PSA (12.1%). 104 Before the pandemic, the most common telehealth modality was video visits; studies reported a high level of satisfaction and found that they were an effective and safe means of conducting follow-up visits. 105 During COVID-19, one study found that urologists demonstrated the highest use of telehealth visits among surgical specialties during the late pandemic period.…”
Section: Telehealth Modalitiesmentioning
confidence: 99%
“… 103 A study of a single institution’s VA data found that the most common reasons for urologic telehealth referrals were sexual dysfunction (26.8%), lower urinary tract symptoms (20.6%), hematuria (15.0%), prostate cancer (13.3%), and elevated PSA (12.1%). 104 Before the pandemic, the most common telehealth modality was video visits; studies reported a high level of satisfaction and found that they were an effective and safe means of conducting follow-up visits. 105 During COVID-19, one study found that urologists demonstrated the highest use of telehealth visits among surgical specialties during the late pandemic period.…”
Section: Telehealth Modalitiesmentioning
confidence: 99%
“…Telehealth was utilized for a wide range of diseases and often used in conjunction with primary care (PC) and urologic Faceto-Face (FTF) visits to deliver complete care. The most common urologic conditions evaluated during the initial telehealth meeting (including both general urology and sexual dysfunction clinics) were sexual dysfunction 26.8% (217/811), LUTS 20.6% (167/811), hematuria 15.0% (122/811), prostate cancer 13.3% (108/811), and an elevated PSA 12.1% (98/811) [7]. Urology Virtual clinics are a promising new platform which can offer clinical, financial and environmental benefits to support an increasing urological referral burden.…”
mentioning
confidence: 99%